Genome-wide identification and expression analysis of the calmodulin-binding transcription activator (CAMTA) gene family in wheat (Triticum aestivum L.) - Fan Yang; Fu-shuang Dong; Fang-hui Hu; Yong-wei Liu; Jian-fang Chai; He Zhao; Meng-yu Lv; Shuo Zhou (BMC Genetics, 2020)
Abstract Background Plant calmodulin-binding transcription activator (CAMTA) proteins play important roles in hormone signal transduction, developmental regulation, and environmental stress tolerance. However, in wheat, the CAMTA gene family has not been systematically characterized. Results In this work, 15 wheat CAMTA genes were identified using a genome-wide search method. Their chromosome location, physicochemical properties, subcellular localization, gene structure, protein domain, and promoter cis-elements were systematically analyzed. Phylogenetic analysis classified the TaCAMTA genes into three groups (groups A, B, and C), numbered 7, 6, and 2, respectively. The results showed that most TaCAMTA genes contained stress-related cis-elements. Finally, to obtain tissue-specific and stress-responsive candidates, the expression profiles of the TaCAMTAs in various tissues and under biotic and abiotic stresses were investigated. Tissue-specific expression analysis showed that all of the 15 TaCAMTA genes were expressed in multiple tissues with different expression levels, as well as under abiotic stress, the expressions of each TaCAMTA gene could respond to at least one abiotic stress. It also found that 584 genes in wheat genome were predicted to be potential target genes by CAMTA, demonstrating that CAMTA can be widely involved in plant development and growth, as well as coping with stresses. Conclusions This work systematically identified the CAMTA gene family in wheat at the whole-genome-wide level, providing important candidates for further functional analysis in developmental regulation and the stress response in wheat.